THE EFFECT OF THE USE OF PROBLEM BASED LEARNING MODEL TO THE CRITICAL THINKING SKILL OF STUDENT IN SOCIAL STUDIES LEARNING (Quasi Experimental Research in VII grade of 1 Lembang Junior High School) - Karlina, Nining (Universitas Pendidikan Indonesia, 2017)
Abstract-this study aims to know, analyze and evaluate the differences of studentsâ€™ critical thinking skills by using problem based learning model and conventional models. This study uses a quasi-experimental method with quantitative approach using Nonequivalent (Pretest-Posttest) Control-Group Design. The data collection technique used in this study is using the test. The data analysis technique is done by independent t-test sample. Moreover, this research shows the significant differences if seen from the average of percentage ofÂ experiment class; pretest is less while posttest is so gratified. The result of pretest control class is less and posttest is enough The results of this research give the recommendation for teachers and next researchers to apply problem based learning model to enhance critical thinking ability of students. In addition, problem based learning model is also expected to encourage students to be able to solve problems encountered in everyday life, especially in social studies.Keywords: Problem based learning, conventional learning model and critical thinking.